2016
DOI: 10.3389/fimmu.2016.00486
|View full text |Cite
|
Sign up to set email alerts
|

ω3 Polyunsaturated Fatty Acids as Immunomodulators in Colorectal Cancer: New Potential Role in Adjuvant Therapies

Abstract: Diet composition may affect the onset and progression of chronic degenerative diseases, including cancer, whose pathogenesis relies on inflammatory processes. Growing evidence indicates that diet and its components critically contribute to human health, affecting the immune system, secretion of adipokines, and metabolic pathways. Colorectal cancer (CRC) is one of the leading causes of death worldwide. Antineoplastic drugs are widely used for CRC treatment, but drug resistance and/or off-target toxicity limit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 83 publications
2
24
0
1
Order By: Relevance
“…While newly approved immunotherapeutic agents for treating MSI tumors has shown great promise, the clinical efficacy remains suboptimal, with a response rate of 30–50% in the recent phase II trials . Therefore, given the well‐known immunomodulatory activity and the observed benefit of MO3PUFA for MSI tumors in our studies, it is possible that integrating MO3PUFA into the current immunotherapeutic regimen may help improve treatment outcome …”
Section: Discussionmentioning
confidence: 91%
“…While newly approved immunotherapeutic agents for treating MSI tumors has shown great promise, the clinical efficacy remains suboptimal, with a response rate of 30–50% in the recent phase II trials . Therefore, given the well‐known immunomodulatory activity and the observed benefit of MO3PUFA for MSI tumors in our studies, it is possible that integrating MO3PUFA into the current immunotherapeutic regimen may help improve treatment outcome …”
Section: Discussionmentioning
confidence: 91%
“…159 However, regulation of host immune surveillance as a mechanism of primary CRC chemoprevention activity remains a valid hypothesis for both seAFOod trial interventions. 160 We have recently reported that mixed ω-3 PUFA treatment is associated with an increase in abundance of SCFA-producing bacteria in the colon. 129 The hypothesis that the propensity for EPA benefit in the distal colorectum relates to increased anticarcinogenic SCFA-FFAR2 signalling 132 should now be tested by measuring stool SCFA concentrations in human studies, in parallel with FFAR2 expression studies using rectal mucosa from the seAFOod trial biobank.…”
Section: Recommendations For Researchmentioning
confidence: 96%
“…Given the important role of lipids at various levels of cell physiology, changes in their metabolism may interfere with a variety of processes, e.g., the control of the plasticity and organization of plasma membranes, or the provision of substrates for ATP synthesis and cell signaling [3]. Some authors have claimed a positive effect of supplementation with various lipids [2,6] or their main structural elements, fatty acids (FAs), in cancer patients [7]. However, the effects of FAs were also shown to depend on the structural group they belong, as well as on their source (de novo synthesis, diet) [3].…”
Section: Introductionmentioning
confidence: 99%